Synthesis and characterisation of manganese ferrite oxides for use in pseudocapacitive super capacitors as electrode materials - Quah, Ivan Tian Min (2016)
Manganese Ferrite Oxides were synthesis in a bid to ascertain their specific capacitance for the use as supercapacitor electrodes. 5 samples of varying composition in the form of MnxFe3-xO4 were synthesised via chemical co-precipitation and post-annealing. Said 5 samples had x values of 0.5, 1, 1.5, 2 and 2.5 and were put under electrochemical and materials characterisation using techniques such as cyclic voltammetry, TEM and XRD. The cyclic voltammetry was conducted using a 3 electrode system with 1M of KOH as the electrolyte. The highest specific capacitance measured was from Mn1.5Fe1.5O4 of 114.35 F/g and an increasing trend was observed for the first 3 samples, namely Mn0.5Fe2.5O4, MnFe2O4 and Mn1.5Fe1.5O4. A decrease in Cs was subsequently observed for the next sample followed by an increase for the last sample. Said phenomena of decrease/increase could not be adequately explained however, to explain the phenomena; several reasons were put forward such as, insufficient amount of Mn3+ and Fe3+ ions and the presence of an unidentified phase.